2019
DOI: 10.1002/lary.28163
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of head and neck surgery in patients with a history of solid organ transplantation

Abstract: Objectives/Hypothesis Examine the prevalence and outcomes of head and neck surgeries in patients with a history of organ transplantation. Study Design A retrospective cross‐sectional analysis utilizing the Nationwide Readmissions Database, 2010 to 2014. Methods The study population included adults patients who underwent head and neck surgeries. Patients with a reported history of solid organ transplantation were compared to patients with no such history. Results The study population included 322 transplant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…On the other hand, the incidences of HPV-related cancers (laryngeal and oropharyngeal cancers) and EBV-related cancers (nasopharyngeal cancer) were similar in HIV-infected patients, and in organ recipients in this study [36]. Various researches presented co-carcinogenic influence of HPV and EBV on oncogenesis in oral cavity, oro-and nasopharynx, and larynx [32,34,35]. Among head and neck cancers, especially high incidence of oral and oropharyngeal cancers after solid organ transplantation was observed [5,37].…”
Section: Malignancy In the Head And Neck Areasupporting
confidence: 48%
See 2 more Smart Citations
“…On the other hand, the incidences of HPV-related cancers (laryngeal and oropharyngeal cancers) and EBV-related cancers (nasopharyngeal cancer) were similar in HIV-infected patients, and in organ recipients in this study [36]. Various researches presented co-carcinogenic influence of HPV and EBV on oncogenesis in oral cavity, oro-and nasopharynx, and larynx [32,34,35]. Among head and neck cancers, especially high incidence of oral and oropharyngeal cancers after solid organ transplantation was observed [5,37].…”
Section: Malignancy In the Head And Neck Areasupporting
confidence: 48%
“…This study analyzing the 10 years follow-up period reported that 80% of all head and neck cancers were of cutaneous type [34]. The significant increase in the prevalence of several head and neck tumors after kidney transplant, namely oral, salivary and non-melanoma skin cancer was found by Al-Qurayshi et al [35]. Nevertheless, it was reported that in otolaryngology practice, RTRs were predisposed to develop head and neck squamous cell carcinoma (HNSSC) both related and unrelated to a latent viral infection [35].…”
Section: Malignancy In the Head And Neck Areamentioning
confidence: 84%
See 1 more Smart Citation
“…PJI is the most feared complication following arthroplasty in SOT patients given the hypothesized higher risk posed by the use of chronic immunosuppressive medications in these patients. However, across surgical specialties, in comparative studies of elective surgical procedures adjusting for underlying medical comorbidity, SOT patients have similar rates of post-operative infections and wound complications [ 22 , 23 ]. Prior studies on complications following TJA in SOT patients have also not conclusively shown an increased risk [ 5 , [24] , [25] , [26] , [27] ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a retrospective cohort study based on the Nationwide Readmission Database (NRD) from 2010 to 2017. NRD is part of the Healthcare Cost and Utilization Project (HCUP) covers 57.8% of the entire United States population, and is used to assess the cost and quality of healthcare services (8). The NRD database contains the following information: sociodemographic information, data about the diagnosis and procedures at hospitalization admission based on the International Classification of Diagnosis Ninth and Tenth Revision (ICD-9 and ICD-10) codes, and in-patient outcomes (Table S1).…”
Section: Data Sourcementioning
confidence: 99%